An Overview of the Business Environment Around the Globe Through the Means of the PESTEL Analysis Framework – The Example of the Renewable Energy - Димитров, Иван (Научни трудове, 2024)
The international environment is changing at an ever-accelerating pace and there are new challenges facing the global economy on a daily basis. In this paper we will provide a brief overview of the major changes in the international business environment using the PESTEL analysis framework with the help of analysis and synthesis of several previous publications. Additionally, examples are provided in order to show how these changes are affecting the development of renewable energy. As a result of this overview, forecasts are also given for the future impact of renewable energy on the global economy.